Resources for Indigenous Theology from a Sami Perspective - Jernsletten, Jorunn (The ecumenical review, 2010)
By looking at resources for indigenous theology, this article focuses on some key concepts in Sami tradition and how they are linked to a native understanding of the Christian concept of creation. An important aspect is the reciprocity between human beings and other beings or “creations”. The article takes the biblical injunction to love one's neighbour as challenged through Sami spirituality and theology to apply also to how one should behave towards other beings.